Diseño de un sistema de gestión integrados de calidad y ambiente en el centro de servicios técnicos y transferencia tecnológica ambiental de la ESPOCH según las normas ISO 9001:2008 e ISO 14001:2004 - Erazo Veloz, Marcela (2015)
This research was conducted at the Center for Technical Services and Environmental Technology Transfer (CESTTA) located in the city of Riobamba. The main objective is to develop an Integrated Management System for Quality and Environment according to ISO 9001: 2008 and ISO 14001: 2004, and improve the processes of quality management and environment.